GLP-1R–GIPR–PPARα/γ/δ quintuple agonism corrects obesity and diabetes in mice - Daniela Liskiewicz; Aaron Novikoff; Ahmed Khalil; Seun Akindehin; Jonathan E. Campbell; Pietra Candela; Russell L. Castelino; Callum Coupland; Maxime Culot; W. Scott Dodson; Jonathan D. Douros; Hannes Embring; et al. (Nature, 2026)
Abstract There are increasing numbers of effective drugs to improve obesity-linked metabolic dysfunction; GLP-1R–GIPR co-agonism is effective in the management of obesity and type 2 diabetes 1,2 , and lanifibranor—a nuclear-acting small-molecule triple agonist of PPARα, PPARγ and PPARδ—is in clinical phase 3 trials for the treatment of metabolic dysfunction-associated steatohepatitis 3 . Here, seeking to further improve the metabolic efficacy of GLP-1R–GIPR co-agonism, we report the development of a unimolecular quintuple agonist that combines the body weight-reducing and blood glucose-lowering effects of GLP-1R–GIPR co-agonism with the insulin-sensitizing and anti-inflammatory effects of lanifibranor via its targeted delivery into GLP-1R- and GIPR-expressing cells. In vitro, GLP-1–GIP–lanifibranor is indistinguishable from GLP-1–GIP in relation to incretin receptor signalling and shows equal stimulation of insulin secretion in isolated mouse islets. In vivo, however, GLP-1–GIP–lanifibranor outperforms GLP-1R–GIPR co-agonism and semaglutide, further decreasing body weight, food intake and hyperglycaemia in obese and insulin-resistant mice through synergistic incretin and PPAR action. The metabolic action of GLP-1–GIP–lanifibranor is blunted in mice with genetic or pharmacological inhibition of GLP-1R, GIPR or PPARδ and is absent in DIO double incretin receptor-knockout mice, collectively suggesting that GLP-1–GIP–lanifibranor has substantial therapeutic value in the treatment of obesity and diabetes.